PENGEMBANGAN SOP (STANDART OPERATIONAL PROCEDURE) LABORATORIUM DALAM RANGKA OPTIMALISASI FUNGSI LABORATORIUM PADA PROGRAM STUDI PENDIDIKAN TATA BUSANA UNNES - Sholikhah, Roudlotus; Suci, Puji Hujria (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2020)
The Fashion Design Education Study Program is one of the study programs in the Faculty of Engineering, Universitas Negeri Semarang. In learning at the Fashion Design Education Study Program, 70% of learning is practical learning. In the Fashion Design Education Study Program, the researcher found that the laboratory management was still not optimal due to several problems, including the laboratory management which was still manual and not properly organized according to standards. This problem has inspired researchers to develop laboratory management for the Fashion Design Education Study Program in the Home Economic Department, Faculty of Engineering, Universitas Negeri Semarang. It is hoped that the results of this research will produce SOP (standart operational procedure) products that improve the laboratory management of the Fashion Design Education Study Program so that they can develop better and have clear measurement standards. This study used a development research design (Gall and Borg, 1983). This development research procedure consists of 6 stages, namely determining, identifying problems, reviewing various laboratory SOP, developing prototypes, expert reviews and testing SOP prototypes, and revising development products. The results of this research are (1) Several SOP products, including: SOP for the preparation of laboratory use schedules, SOP for the use of laboratory equipment, SOP for the use of laboratory equipment, SOP for borrowing laboratory equipment/ goods/ facilities and infrastructure, SOP for the use of laboratory equipment, SOP for maintenance of laboratory equipment. , SOP for maintenance and repair of Laboratory Equipment, and SOP for monitoring and evaluation of Laboratory; (2) The feasibility of laboratory SOP by laboratory management experts is considered feasible to be tested and used for Laboratory SOP with several suggestions for revisions, with a percentage rate of 78% for the first expert, and 83% for the second expert; and (3) The results of the feasibility of the SOP for the Laboratory of Fashion Design Education Study Program, Home Economic Department, Faculty of Engineering, Universitas Negeri Semarang, after being tested on laboratory assistants, practical lecturers and students, were assessed that the SOP was very suitable to be used in the Laboratory of the Fashion Design Education Study Program Universitas Negeri Semarang. The percentage level of testing to the laboratory assistant is 93%, practical lecturers 88% and students 95% with no revision respectively.